2014
DOI: 10.1002/pssa.201330365
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of MEA‐based nanocavity sensor arrays for extracellular recording of action potentials

Abstract: Nanocavity sensor arrays are powerful devices for parallel extracellular recordings of action potentials from cell networks. The sensors combine a high spatial resolution and seal resistance between cell and electrode with low electrode impedances, allowing low‐noise electrophysiological measurements of individual cells in a network without the use of CMOS technology. In this paper, we present a new protocol for the simple fabrication of nanocavity sensors, which enables easy modification of standard microelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…Integration of sensors in various scaffold materials has been successfully demonstrated in several studies. [10,11,[25][26][27] However, fabricating scaffolds with integrated sensors for tissue engineering is usually a time-consuming, complex process, requiring multiple steps. Alternatively, electrospun poly(vinylidene fluoride) (PVDF)based piezoelectric fiber sheets are flexible, low cost, lightweight, and biocompatible, and can serve both as scaffolds and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of sensors in various scaffold materials has been successfully demonstrated in several studies. [10,11,[25][26][27] However, fabricating scaffolds with integrated sensors for tissue engineering is usually a time-consuming, complex process, requiring multiple steps. Alternatively, electrospun poly(vinylidene fluoride) (PVDF)based piezoelectric fiber sheets are flexible, low cost, lightweight, and biocompatible, and can serve both as scaffolds and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocavity arrays have been presented as a method to efficiently combine the need for a large electrode area with a high spatial resolution. [38][39][40] This sensor type consists of a welldefined cavity between electrode and passivation layer and a small opening aperture that connects the cavity to the cell. Consequently, similar to the planar patch clamp method, 41,42 a low sensor impedance is combined with a high spatial resolution at the single-cell level.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have presented planar nanocavity sensors based on sacrificial layer etching, which exhibited low electrical impedance combined with good recording capabilities of action potentials. 38,40 In this study, we introduce a new cavity device with a nanostructured electrode interface. We investigate electrical impedance and cell-sensor coupling for stimulation applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wolfrum et al overcame this dilemma by creating micropores that interface the cells to larger electrodes. 10,11 A third approach involves decreasing the membrane impedance at the cell-electrode junction. In practice, this involves transiently rapturing the cell membrane by applying a zap voltage to a nanostructured electrode, thus allowing the electrodes to enter the cell and perform pseudo-intracellular recording until the raptured membrane reorganizes.…”
mentioning
confidence: 99%
“…For example, Czeschik et al used nanocavity electrodes and reported recordings of up to $3 mV from cardiomyocytes. 11 The signal amplitude would be expected to be further amplified by incorporating the resistive sheet covering method.…”
mentioning
confidence: 99%